Change in prevalence of self-harm from 2002 to 2018 among Norwegian adolescents. (5th March 2020) - Tørmoen, Anita J; Myhre, Martin; Walby, Fredrik A; Grøholt, Berit; Rossow, Ingeborg
Abstract: Background: Self-harm is prevalent among adolescents and associated with mental health problems and negative life-events. Few studies have examined changes in its prevalence related to these factors. This study explored whether changes in prevalence of self-harm among adolescents had occurred, and to what extent changes in associated factors may have contributed. Methods: Two cross-sectional school-based surveys among adolescents (grades 8–10) in Norway were conducted in 2002 ( N  =   5842) and in 2017/18 ( N  =   29 063). Past year prevalence of self-harm and identical variables on risk factors was analyzed in hierarchical logistic regression to examine whether and to what extent changes in self-harm correlates could explain periodical change in prevalence of self-harm. Results: An increase from 4.1% to 16.2% in self-harm prevalence was observed from 2002 to 2017/18. The increase was relatively larger among girls compared to boys and among 8th graders compared to 10th graders. Among the assessed risk factors for self-harm, depressive symptoms increased, while anti-social behavior, exposure to violent acts and drinking to intoxication decreased. The increase in depressive symptoms contributed to explain increase in self-harm. This contribution was outweighed by the decrease in other risk factors. Conclusions: Self-harm prevalence increased 4-fold among Norwegian adolescents over a 15-year period. While exposure to several risk factors for self-harm changed substantially in this period, these risk factors could in sum not explain any of the increase in self-harm.